1990
DOI: 10.1007/bf00403323
|View full text |Cite
|
Sign up to set email alerts
|

A search for the presence of the enteroviral capsid protein VP1 in pancreases of patients with Type 1 (insulin-dependent) diabetes and pancreases and hearts of infants who died of coxsackieviral myocarditis

Abstract: Using an antiserum raised to a recombinant coxsackie virus B 3 capsid protein, VP1, an immunocytochemical technique was developed which was capable of detecting the presence of all coxsackie B viruses in formalin fixed paraffin embedded infected tissue culture cells. This technique was tested on autopsy heart and pancreas from 21 patients who were thought to have died of acute coxsackievirus B myocarditis. Cardiac myocytes were positive for the VP1 protein in 12 of 20 cases where the heart was available for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
72
1
4

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 23 publications
7
72
1
4
Order By: Relevance
“…CAR production in islet cells, as observed in this study, confirms a previous report on islet-specific production of this molecule in normal human pancreatic islets [C. Verbeke and G. E. Blair, unpublished results]. This finding fits well with previous observations indicating clear tropism of enterovirus for human islets in patients who died of systemic enterovirus infection or diabetic ketoacidosis; the virus has been repeatedly discovered specifically in the islets, but not in the exocrine pancreas [4,20,24]. In addition, enteroviruses infect human islets in vitro.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…CAR production in islet cells, as observed in this study, confirms a previous report on islet-specific production of this molecule in normal human pancreatic islets [C. Verbeke and G. E. Blair, unpublished results]. This finding fits well with previous observations indicating clear tropism of enterovirus for human islets in patients who died of systemic enterovirus infection or diabetic ketoacidosis; the virus has been repeatedly discovered specifically in the islets, but not in the exocrine pancreas [4,20,24]. In addition, enteroviruses infect human islets in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…The enterovirus-specific antibody (clone 5-D8/1) has been previously used in studies showing enteroviruses in the pancreas of diabetic patients and in the heart tissue of patients with dilated cardiomyopathy [21,22,24]. Even though its specificity has been demonstrated in these studies, it has also been shown that antibodies against enterovirus VP1 protein may cross-react with heat shock proteins, especially HSP60 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy pancreases from 12 newborn infants who died of fulminant coxsackievirus infections at the age of 3 days to 10 months [48] were studied for presence of enteroviral ribonucleic acid (RNA) by in situ hybridisation. Most of these patients had coxsackievirus myocarditis and six out of seven enterovirus-positive pancreases showed evidence of insulitis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, 40 non-diabetic pancreases from subjects matched for age and sex were included in the study as controls. Autopsy specimens obtained from [48] and the University of Tübingen were treated as anonymous tissue, and studies carried out in accordance with the Declaration of Helsinki of the World Medical Assembly. According to the statement of the ethics committee of the University of Tübingen this kind of historic study can be done without specific permissions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation